2022
DOI: 10.1002/rth2.12727
|View full text |Cite
|
Sign up to set email alerts
|

“If I wasn't a girl”: Experiences of adolescent girls with heavy menstrual bleeding and inherited bleeding disorders

Abstract: Background: Heavy menstrual bleeding (HMB) is a presenting symptom of an inherited bleeding disorder (BD) and results in hospitalizations, limitations of daily activities, and a reduction in quality of life. Adult women with BD report a sense of stigma, difficulties understanding their bleeding, and challenges with diagnostic labels. The experiences of adolescents with HMB and BD are unknown despite advances in medical management through the rapidly growing network of young women's hematology programs. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…In accordance with prior research, our respondents indicated a lack of awareness and delay in diagnosis of underlying bleeding tendency in patients with HMB and plead for improving patient empowerment [22,[29][30][31] . Parker et al interviewed adolescents who describe the burden HMB gives on their identities and social quality of life, causing stress, anxiety and feelings of being "left out" [30] . Given the greater impact HMB has on the quality of life of (young) women, obtaining an accurate and timely diagnosis can lead to identity building and empowerment [22] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with prior research, our respondents indicated a lack of awareness and delay in diagnosis of underlying bleeding tendency in patients with HMB and plead for improving patient empowerment [22,[29][30][31] . Parker et al interviewed adolescents who describe the burden HMB gives on their identities and social quality of life, causing stress, anxiety and feelings of being "left out" [30] . Given the greater impact HMB has on the quality of life of (young) women, obtaining an accurate and timely diagnosis can lead to identity building and empowerment [22] .…”
Section: Discussionsupporting
confidence: 82%
“…HMB has a profound effect on the quality of life due to the severe bleedings [27,28] . In accordance with prior research, our respondents indicated a lack of awareness and delay in diagnosis of underlying bleeding tendency in patients with HMB and plead for improving patient empowerment [22,[29][30][31] . Parker et al interviewed adolescents who describe the burden HMB gives on their identities and social quality of life, causing stress, anxiety and feelings of being "left out" [30] .…”
Section: Discussionsupporting
confidence: 82%
“…must also be considered as the health disparities for these populations are often compounded [ 117 ]. Some PWIBD feel a sense of ‘otherness’ or stigma due to their BD [ 118 , 119 ]; socially disadvantaged PWIBD may experience further isolation. The necessary DEI conversations and initiatives require all individuals to think critically and challenge their own assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings chime with work previously conducted in women with HMB, with or without a bleeding disorder, with similar themes emerging from the interviews. Parker et al’s [ 12 ] study of adolescent girls with a bleeding disorder and HMB identified the following themes: anxiety and embarrassment, isolation, increased cautiousness, and planning. Dutton and Kai [ 13 ] reported on women’s experiences of HMB and their medical treatment up to 10 years after the initial management in general practice.…”
Section: Discussionmentioning
confidence: 99%